Effects of fish skin collagen peptide and freezing on rheology, water distribution, structure, and digestibility of starch within wheat dough - Jiaxin Duan; Lijuan Wang; Hao Guo; Zhouya Bai; Yuanyuan Chen; Chonghui Yue; Guoqiang Zhang; Yujing Xu; Ping Wang; Sihai Han; Jinying Guo (Food Hydrocolloids, 2026)

Direct-contact ultrasound pretreatment of whole wheat flour-water mixtures: Enhancing dough processability and noodle antioxidant capacity - Menghan Chang; Xin Wang; Chonghui Yue; Yingbo Zhao; Yuanyuan Chen; Zhouya Bai; Peiyan Li; Denglin Luo; Sihai Han (Journal of Cereal Science, 2026)

Ultrasonic pretreatment of batter: A method for improving soft bread quality and storage characteristics - Tiantian Wang; Kaili Meng; Baotai Yuan; Denglin Luo; Zhouya Bai; Chonghui Yue; Peiyan Li; Yuanyuan Chen; Sihai Han (Journal of Cereal Science, 2026)

Capability heterogeneity and dual technological paths: a micro-level empirical analysis of TFP improvement in Chinese marine enterprises - Shuiping Yao; Wenjie Jin; Yan Chen; Yi Shi; Chonghui Zhang (Frontiers in Marine Science, 2026)
Against the backdrop of the global marine economy's transition toward innovation-driven development, the selection of technological upgrading paths is a critical step for marine enterprises to achieve total factor productivity (TFP) improvement. Based on Chinese enterprise tax survey data from 2016 to 2020, this paper integrates independent research and development (R&D) and external equipment procurement into a unified analytical framework, using multiple econometric and causal identification models to systematically examine the internal mechanisms through which these dual technological paths drive TFP improvement in marine enterprises. The results indicate that both independent R&D and external equipment procurement significantly enhance the TFP of marine enterprises, exhibiting a substantial positive synergistic effect. Furthermore, the driving effects of these two paths on TFP are subject to dual threshold constraints related to enterprise resource boundaries. When an enterprise’s internal business diversification degree or external energy consumption intensity crosses critical thresholds, the marginal returns of technological output demonstrate a non-linear, regime-switching characteristic of structural decline. Finally, employing a multiply robust causal identification model, this paper reveals optimal strategic differentiation under capability heterogeneity constraints: the optimal decision-making of high-tech enterprises converges on a dual synergistic path, whereas non-high-tech enterprises, constrained by higher endogenous innovation costs, adopt the single path of external equipment procurement as their rational dominant strategy. This study enriches the micro-level empirical evidence regarding technological progress and productivity improvement in the marine industry, providing a theoretical reference for the formulation of differentiated innovation support policies.

Integrated analysis of circRNA- and lncRNA-mediated ceRNA regulatory networks reveals early immune responses induced by Vibrio anguillarum vaccine in turbot (Scophthalmus maximus) intestine - Chonghui Chen; Beibei Wang; Yiying Liu; Pei Zhang; Xiaoxu Zhang; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2026)

Identification, immunological function, and antimicrobial mechanisms of CXCL12 in turbot (Scophthalmus maximus) - Xiaoxu Zhang; Beibei Wang; Yiying Liu; Pei Zhang; Chonghui Chen; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2026)

Mechanism of ultrasound-modulated gluten-inulin interactions: Impact of inulin polymerization degree - Zhouya Bai; Jiahao Wan; Wenhui Deng; Yanbin Wang; Yuanyuan Chen; Peiyan Li; Chonghui Yue; Denglin Luo (Food Research International, 2026)

Modulating hydrated wheat gluten network structure with different types of polysaccharides: unraveling interaction mechanisms - Ziyu Wang; Xin Wang; Haosen Zeng; Chonghui Yue; Yuanyuan Chen; Libo Wang; Sihai Han; Peiyan Li; Zhouya Bai; Denglin Luo (Food Research International, 2026)

Adaptive NHC-assisted GNSS/INS tightly coupled vehicle navigation method based on an SE23-EKF - Hanxu Li; Shaojie Chen; Yueyuan Ma; Hao Wu; Chonghui Li; Zihao Liu; Conghai Ruan (Advances in Space Research, 2026)

Investigating the effects of different types of polysaccharides on the moisture distribution, rheology and structural properties of ferulic acid-enriched dough - Menghan Chang; Chonghui Yue; Xinyu Bo; Xin Wang; Zhouya Bai; Yuanyuan Chen; Peiyan Li; Jinying Guo; Denglin Luo (Journal of Cereal Science, 2026)

Functional characterization of two CCL20 chemokines in black rockfish (Sebastes schlegelii): dual roles in immune cell recruitment and direct antimicrobial defense - Fengjun Lin; Yiying Liu; Chonghui Chen; Xiaoxu Zhang; Pei Zhang; Huijun Huo; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2025)

Impact of diphosphate esterification on quality characteristics of high-content inulin-enriched dough - Hui Wang; Qiang Chen; Denglin Luo; Chonghui Yue; Peiyan Li; Libo Wang; Sihai Han; Kangyi Zhang; Zhouya Bai (Journal of Cereal Science, 2025)

Estimating strong point CO2 emissions by combining spaceborne IPDA lidar and HSRL - Chonghui Cheng; Dong Liu; Shuaibo Wang; Xingying Zhang; Lu Zhang; Weibiao Chen; Jiqiao Liu; Xueping Wan; Wentai Chen; Xiaolong Chen; Jingxin Zhang; Jiesong Deng; et al. (Remote Sensing of Environment, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Early life imidacloprid and copper exposure affects the gut microbiome, metabolism, and learning ability of honey bees (Apis mellifera) - Xijie Li; Qihe Tang; Mengshang Hou; Yantao Pang; Dan Li; Yajuan Chen; Richan Fang; Yi Deng; Jun Zhang; Chonghui Zhao; Junjie Li; Yuan Chen; et al. (Environmental Research, 2025)

Constructing dual active sites modified crystalline carbon nitride with diminished excitation binding energy for overall photosynthesis of H2O2 - Lei Zeng; Chonghui Jiang; Yueyang Tan; Wei Yang; Qiushi Hu; Xihan Chen; Yabin Jiang; Yang-Gang Wang; Wulin Song; Limin Huang (Chemical Engineering Journal, 2025)

Development of China's atmospheric environment monitoring satellite CO2 IPDA lidar retrieval algorithm based on airborne campaigns - Shuaibo Wang; Chonghui Cheng; Sijie Chen; Jiqiao Liu; Xingying Zhang; Lingbing Bu; Jingxin Zhang; Kai Zhang; Jiesong Deng; Wentao Xu; Weibiao Chen; Dong Liu (Remote Sensing of Environment, 2024)

Smart windows based on ultraviolet-B persistent luminescence phosphors for bacterial inhibition and food preservation - Xiaohui Lin; Chonghui Li; Shicai Xu; Jihua Wang; Huanxin Yang; Yikai Qu; Qingshuai Chen; Zhenghua Li; Mengyu Su; Guofeng Liu; Hanping Liu; Jilei Yang; et al. (Food Chemistry, 2024)

Genetic diversity of RNA viruses infecting invertebrate pests of rice - Haoran Wang; Shufen Chao; Qing Yan; Shu Zhang; Guoqing Chen; Chonghui Mao; Yang Hu; Fengquan Yu; Shuo Wang; Liang Lv; Baojun Yang; Jiachun He; et al. (Science China Life Sciences, 2024)

Effective sulfide flotation of cerussite by using trithiocyanuric acid as a novel sulfurizing reagent - Jiwei Xue; Yaoben Qu; Yao Chen; Chonghui Zhang; Xianzhong Bu (Minerals Engineering, 2023)

Optimization of the OCO-2 Cloud Screening Algorithm and Evaluation against MODIS and TCCON Measurements over Land Surfaces in Europe and Japan - Sijie Chen; Shuaibo Wang; Lin Su; Changzhe Dong; Ju Ke; Zhuofan Zheng; Chonghui Cheng; Bowen Tong; Dong Liu (Advances in Atmospheric Sciences, 2020)

Simultaneous determination of clavulanic acid and tazobactam in bovine milk by HPLC - Peipei Guo; Yuan Chen; Chonghui Yue; Guoping Yu (Food Additives & Contaminants: Part A, 2017)

Quality evaluation of snow lotus (Saussurea): quantitative chemical analysis and antioxidant activity assessment - Jian Qiu; Xiaofeng Xue; Fudong Chen; Chonghui Li; Nuer Bolat; Xiaojun Wang; Yuzhen Baima; Qiao Zhao; Dexiu Zhao; Fengshan Ma (Plant Cell Reports, 2010)